Climate change threatens water resources over the Qinghai-Tibetan plateau - Xianghui Cao; Zhen Zhao; Yuejun Zheng; Chao Su; Qiuliang Lei; Wenpeng Li; Chunyan Li (Scientific Reports)
Abstract The availability and transport of water resources across the Qinghai-Tibetan Plateau (QTP), a water tower in Asia, is vital in affecting downstream region. Significant climate warming has altered the water balance of QTP and influenced downstream water resources, and the dynamics of water resources and its key influencing factors remain unknown in this region. To deepen our understanding of water resource status over the QTP, here we comprehensively summarized the variations in precipitation and water resources (glaciers, lakes, runoff and terrestrial water storage) in the past few decades by integrating long-term multi-source remote sensing and monitoring data. Annual precipitation displayed a significant increase over the QTP from 1961 to 2023 (4.3 mm per decade; P < 0.05). The decrease of glacial area was the dominant trend on the QTP from 1976 to 2024, and the decline rate has reached 58.37%. The area of lakes increased from 960 km2 in 1960 to 1919 km2 in 2020, indicating a clear expansion. The surface runoff increased from 4089.73 × 108 m3 in 1961 to 5788.63 × 108 m3 in 2018, with a growth rate of 11.94 × 108 m3/yr. Terrestrial water storage change (TWSC) showed a decreasing trend from 2019 to 2023 (R 2 = 0.3636*, P < 0.05), which suggested that future expansion of the terrestrial water storage (TWS) deficit may occur. Affected by climate warming, the outcome that the lakes will display a continuous expansion and glacier also will continue to retreat on the QTP could be expected. If melting water from glaciers ablation cannot offset the demand for water resources, this may have serious socio-economic and ecological threats to the region. Thus, it is essential to take the continuous monitoring of water resources over the QTP as a pressing priority, providing adaptation strategies for these highly fragile areas.